Diseño de un programa de disciplina operativa para la mejora de los procesos operacionales en actividades de Workover en la Cuenca del Valle Superior de Magdalena (2019)
The aim of the present article is to order to design an operational discipline program for the improvement of the operational processes of the main five workover activities that the Atina Energy Services company developed during 2018, more specifically in the Casabe Field located in the Upper Magdalena Valley Basin. For this purpose, it was necessary to review the flash reports where it was possible to identify that the main activities carried out during 2018 were; tubing in single and double; installation, testing and uninstallation of BOP (Blowout preventer); sand cleaning with a sand pump, and the installation as well as uninstallation of Horse Head. Considering the mentioned data, the technical operability of the equipment involved in these operations was verified and as a result its correct operation was validated. After, the availability and quality stages were developed, leaving the necessary formats and control mechanisms for the correct application of the communication and compliance stages, based on the technical guide of operational discipline of the Pemex company.